Best practice in primary care pathology: review 3 - Smellie, W S A (BMJ Group, 2006)
This best practice review examines four series of common primary care questions in laboratory medicine: (i) “minor” blood platelet count and haemoglobin abnormalities; (ii) diagnosis and monitoring of anaemia caused by iron deficiency; (iii) secondary hyperlipidaemia and hypertriglyceridaemia; and (iv) glycated haemoglobin and microalbumin use in diabetes. The review is presented in question–answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence‐based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. They are not standards, but form a guide to be set in the clinical context. Most of the recommendations are based on consensus rather than evidence. They will be updated periodically to take account of new information.